Survival of Transfused Factor X in Patients with Stuart Disease - Roberts, H. R; Lechler, E; Webster, W. P; Penick, G. D (Thrombosis and Haemostasis, 1965)
These studies show that the intravascular “half-life” of transfused factor X may vary in a single subject from 20% to 42 hours with an average of 32½ hours. Recent previous transfusions into patients with Stuart factor deficiency seem to alter the survival curves of transfused factor X. Extra vascular diffusion of intravascular factor X does occur as demonstrated by appearance of this factor in the lymph of a patient with Stuart disease following transfusion of normal plasma. Apparently the disappearance of factor X is a function of at least two variables; that of extravascular distribution and metabolic destruction. However, factors other than extravascular diffusion may be operative during the accelerated first phase of disappearance.